1997
DOI: 10.1111/j.2044-8287.1997.tb00536.x
|View full text |Cite
|
Sign up to set email alerts
|

Attitude, subjective norm and perceived behavioural control as predictors of women's intentions to take hormone replacement therapy

Abstract: Objectives. To examine women's attitudes towards the use of hormone replacement therapy (HRT) and to predict intention to take it in a sample of 1200 women using the theory of planned behaviour (Ajzen, 1988) and a measure of similar prior behaviour. Design. The design was cross‐sectional. A postal survey was carried out. Methods. Questionnaires were sent to a random sample of 1200 women aged between 38 and 58 generated from the Kent Family Health Services Authority records. Questions based on the theory of pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
38
2
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 24 publications
7
38
2
1
Order By: Relevance
“…In fact, the effect of past behavior on different behavioral intentions of engaging in dissatisfaction responses in high-end restaurants was strongly mediated by one of the TPB variables. Similar results were found in the study by Quine and Rubin (1997) in which perceived behavioral control was shown to have a mediating impact on the relationship between past behavior and the intention of using hormone replacement therapy. Conner and Abraham (2001) also reported that most of the effect of past behavior on intention was mediated rather than direct.…”
Section: Article In Presssupporting
confidence: 89%
“…In fact, the effect of past behavior on different behavioral intentions of engaging in dissatisfaction responses in high-end restaurants was strongly mediated by one of the TPB variables. Similar results were found in the study by Quine and Rubin (1997) in which perceived behavioral control was shown to have a mediating impact on the relationship between past behavior and the intention of using hormone replacement therapy. Conner and Abraham (2001) also reported that most of the effect of past behavior on intention was mediated rather than direct.…”
Section: Article In Presssupporting
confidence: 89%
“…It may be that the previous performance of similar behavior influences intention by mediating perceived behavioral control or one's belief that they can perform these adaptive behaviors [21]. Participants who have performed previous sun-safe behaviors may be able to produce a concrete representation of the performance of such behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…For example, self-efficacy has been shown to play a significant role in expatriates' ability and willingness to adapt to new cultures effectively (Harrison, Chadwick & Scales, 1996); this finding suggests that trainees high in self-efficacy will be more likely to embrace new behaviors necessary to interact in a diversity-friendly environment. Consistent with self-efficacy theory, many TPB researchers have validated the importance of task-specific self-efficacy beliefs to the formation of behavioral intentions (Quine & Rubin, 1997;Wulfert & Wan, 1995). However, research results on similar constructs have been mixed.…”
Section: Hypothesis 5 Employees Who Believe That Their Work Groups Smentioning
confidence: 93%